ANALISIS PEMAHAMAN KONSEP SISWA PADA MATERI POLA BILANGAN - Fatahillah, Arif; Hussen, Saddam; Monalisa, Lioni Anka; Wihardjo, Edy; Priyanti, Nanda Rahma (EDUPEDIA, 2023)
The purpose of learning mathematics is to change the performance of each student in the cognitive, affective and psychomotor domains. One part of the cognitive domain that is needed when studying mathematics is understanding concepts. Hadi and Kasum (2015) reiterated the notion that conceptual understanding is very important in solving mathematical and contextual problems. Based on the results of a preliminary study conducted by researchers at SMPN 1 Krian, information was obtained that students' conceptual understanding was still low, judging from the average daily test results for number pattern material below the KKM. The type of research used in this research is qualitative research. This research was conducted at SMPN 1 Krian. The subjects in this study were two class VIII students of SMPN 1 Krian who had the highest and lowest test results. The data analysis method used in this study consisted of data reduction, data reclassification, and drawing conclusions. The result of this research is that the high subject fulfills the four indicators of understanding the concept which consists of restating a concept, classifying the types of number patterns, applying the concept into a mathematical representation, and selecting certain procedures from a concept. Meanwhile, the low subject did not meet two indicators, namely restating a concept, three indicators fulfilled but not perfect which consisted of classifying the types of number patterns, applying concepts into mathematical representations, and selecting certain procedures from a concept.